Time domain simulation approach for the safe design of small vessels - Wong, Kim Seng (2003)
The conventional statical stability analysis of a ship, which is presented by the righting arm curve, is well known by its simplicity. Unfortunately, the existing stability criteria, which is based on conventional approach does not demand extensive analysis of dynamic effect especially wave forces that is the main cause of capsize. For this reason, in the present study, a safe design guideline of small vessel travelling in waves is proposed to further improve the existing stability criteria. The motion of small vessel in astern seas condition is selected as the most critical situation, where the wave forces can strongly affect its stability and more generally its safety. When a vessel encounters waves from astern, non-linear modes of capsizing is usually observed. Due to the strong influence of non-linearity on the ship motion, Time Domain Simulation approach is required to obtain the ship motion in steps of time. In the analysis, hydrostatic effect is considered as the most important contribution to the ship motion. The hydrostatic terms are calculated up to the free surface. The hydrodynamic forces, which are considered less significant, are predicted by empirical formulas. Two hull forms, namely V bottom hull and round bilge hull are selected to represent the basis hull of small vessels. The reason is the two hull forms are known to have different roll damping and thus have significant effect on roll motions. The well-known Ikeda’s method is studied and modified, so it can be used as a general roll damping prediction method for small vessels. A systematic procedure of parametric study using time domain simulation is presented and the method is used to compare the effect of hull form and environmental parameters on the ship stability. As a conclusion, this study successfully presented safe design guidelines for small vessels operating in astern seas condition and also the effect of ship design parameters on the ship stability